Neuroendocrine tumors (carcinoids) of the stomach and intestines - early diagnosis and minimally invasive endoscopic procedures. - Kuryk, O. G.; Yakovenko, V. O.; Bazdyrev, V. V.; Bodnar, L. V. (Морфологія / Morphologia / Morfologìâ, 2014)
Background. Neuroendocrine tumors of the stomach and intestines are rare diseases. Increasing incidence and complexity of diagnosis of these diseases cause acuteness of the problem. Objective. To evaluate the effectiveness of morphological examination of endoscopic biopsy material for diagnostics of neuroendocrine tumors and for evaluation of completeness of minimally invasive endoscopic surgical interventions (endoscopic mucosal resection and endoscopic submucosal dissection) at neuroendocrine tumors. Methods. On the basis of Medical center "Oberig" in 2009 - 2013 in eight cases neuroendocrine tumors were diagnosed: 2 (25 %) in the stomach, 2 (25%) – in the duodenum, 2 (25%) - in the small intestine, 1 (12.5 %) - in the ascending colon, 1 (12.5%) - in the rectum. Neuroendocrine tumors of stomach and ileum were removed by endoscopic mucosal resection, duodenal bulb and rectum neuroendocrine tumors – by endoscopic submucosal dissection, papillary duodenum, colon and jejunum neuroendocrine tumors – by surgical resection. Results. It was shown, that morphological evaluation of endoscopic mucosal biopsies is effective way to diagnose the neuroendocrine tumors. Conclusion. Endoscopic mucosal resection and endoscopic submucosal dissection allows to get advanced material for morphological diagnosis of neuroendocrine tumors and an adequate method of their removing.